COMPARISON OF FATIGUE PERFORMANCE OF BELOW-KNEE PROSTHETIC SOCKETS FABRICATED VIA NOVEL, DIRECT AND LAMINATION TECHNIQUES - Al-Araji I.Z.H.; Satgunam M.A.P.; Manap A.N.B.A.; Resan K.K.; Muhammad A.K. (Cefin Publishing House, 2025)
Various techniques have been proposed to manufacture prosthetic sockets, which are essential in improving the quality of life among amputees and individuals with special needs. However, the fabrication of prosthetics using the available approaches is uneconomical due to the type of materials utilized during the production, as well as the direct methods that use expensive materials to produce prosthetic parts. Considering this, it is crucial to enhance the direct methods by exploiting cost-effective materials to produce prosthetic parts with desirable behaviors. Therefore, this study aimed to compare the fatigue performance of below-knee (BK) prosthetic sockets manufactured using three different techniques: laminate, direct, and novel. The three sockets specimens were first manufactured. Specimen A was made via the direct method using 4 layers of carbon fiber as the reinforcement and AX140401 as the matrix. Specimen B was also fabricated via the lamination method using 4 layers of carbon fiber as the reinforcement and lamination resin + hardener acrylic as the matrix. Finally, specimen C was made via the direct novel method using 4 layers of carbon as the reinforcement, and the matrix was composed of 20% polyurethane resin (part A: resin, part B: hardener) + 80% acrylic. Subsequently, the pressure distribution at the contact point between the socket and the residual limb was analyzed using the F-SOCKET device. Furthermore, the numerical analysis included the distribution of the stress and the highest internal pressure, the number of cycles ascertained through the utilization of the SOLIDWORKS software. Based on the results, the S-N curves for each specimen show that all three specimens behaved similarly. Using the F-socket, the pressure during the patient's walking cycle reached its highest point at 190 kPa. In addition, applying ground reaction force from the bottom of the direct, lamination, and novel BK prosthetic sockets demonstrated the pressure distribution of the part that reacts to the loading condition. The SOLIDWORKS program revealed from the pressure distribution of the three sockets measured a maximum internal pressure of 191 kPa, 193 kPa, and 191 kPa sequentially, which was close to the pressure within the F-socket. Besides, the number of cycles for the direct, lamination, and novel BK prosthetic sockets was 1,332,345, 1,202,345, and 1,203,567 cycles. In summary, all three specimens fabricated via the direct, lamination, and novel methods achieved similar fatigue performance of BK prosthetic sockets. So, the novel BK prosthetic socket wad designed in which fabricated using a new matrix material was considered acceptable, similar to specimens A and B. ? 2024, Cefin Publishing House. All rights reserved.